Gilbert syndrome: Literature review directed at diagnostic methods (Research, Society and Development, 2023)
Gilbert syndrome is a condition of dominant autosomal inheritance with incomplete penetrance characterized by unconjugated, hyperbilirubinemia in a slightly increased form, chronic and not associated with any liver disease or hemolysis. The carriers of the syndrome have bilirubin glucuronidation disorder and consequent indirect hyperbilirubinemia due to a mutation in the UGT1A1 gene. It usually manifests between the post-pubertal period up to the age of 20 years. The symptoms usually appear after physical exercise, fasting periods, and in infectious conditions. Most patients are asymptomatic, and in some the only sign is jaundice. The diagnosis is given by the elevation of serum bilirubin, rarely exceeds 3 mg/dL, besides anamnesis and directed physical examination. On physical examination, it is essential to investigate the presence of telangiectasia (vascular spider), Dupuytren's contracture (claw hand), gynecomastia, and ascites in order to rule out cirrhosis of the liver. It is also necessary to make sure there is no palpable mass in the right upper quadrant, as this could suggest biliary pathology justifying obstruction jaundice. Gilbert's syndrome has a benign character with favorable prognosis and evolution, being the clinical diagnosis the most important one.